Impacts of huanglongbing on fruit yield and quality and on flushing dynamics of Sicilian lemon trees - Cifuentes-Arenas, Juan Camilo; de Oliveira, Hermes Teixeira; Raiol-Júnior, Laudecir Lemos; de Carvalho, Everton Vieira; Kharfan, Daniela; Creste, André Luís; Gastaminza, Gerardo; Salas, Hernán; Bassanezi, Renato Beozzo; Ayres, Antônio Juliano; Lopes, Silvio Aparecido (Frontiers in Plant Science, 2022)
The severe Asian form of huanglongbing (HLB), a vascular disease associated with the phloem-limited bacterium ‘Candidatus Liberibacter asiaticus’, is transmitted by the Asian citrus psyllid (ACP) Diaphorina citri. Disease impacts are known for sweet oranges and acid limes but not lemons. In a five-year study (2017–2021) we compared yield and fruit quality between naturally-infected and healthy 5-yr-old trees of Sicilian lemon 'Femminello', and shoot phenology on both lemon and ‘Valencia’ orange, both grafted onto ‘Swingle’ citrumelo, grown in southeastern São Paulo State, Brazil. HLB severity (percentage of tree canopy area with HLB symptoms) was assessed every 3–4 months, fruit yield and quality in May (2017 to 2019) or June/July (2020-2021), and vegetative and reproductive shoots fortnightly on 50-cm-long branches. The development of ACP on one-year-old seedlings of five lemon varieties, ‘Tahiti’ acid lime, ‘Valencia’ orange, and orange jasmine was evaluated. Symptoms increased from 11 % in 2017 to 64 % in 2021, and a monomolecular model estimated 10 years for symptoms to occupy >90 % of the tree canopy. On average, production of trees with symptom on 20 %, 50 % or 80 % of the canopy respectively dropped by 18%, 38%, and 53% compared to healthy trees. Fruits of symptomatic branches of lemons were 4.22% lighter and the number of dropped fruits did not correlate with symptom severity. Flushing on symptomatic branches started earlier by 15 to 55 days as compared to the healthy branches of lemon and orange. On diseased trees, vegetative and reproductive shoots respectively increased by 24.5% and 17.5% on lemon and by 67.2% and 70.6% on sweet orange, but fruit set was reduced by 12.9% and 19.7% on lemon and orange trees, respectively. ACP reproduced similarly on all tested plants. The fast symptom progress, significant yield reduction, and earlier flushing on diseased trees, providing conditions highly favorable for the pathogen to spread, reinforce the need of prompt diseased tree removal and frequent ACP preventive control to manage HLB in lemons as in any other citrus crop.